Investigation of Tribological Behaviour on DLC Coatings for AA5051 using DC Sputtering - L. Natrayan; Piyush Gaur; Anjibabu Merneedi; S. Kaliappan; Pravin P. Patil; V. Sivaprakash; Muse Degefe Chewaka (Adsorption Science & Technology)
DLC coatings are deposited on aluminium substrates to improve the wear resistance property of the substrates using sputtering deposition in this study. DLC coatings are deposited using the graphite target onto the Al5051 substrates using DC sputtering. The deposited coatings are then analyzed for their adhesion strength, hardness, coefficient of friction, and chemical compositions. The pin-on-disk method is conducted in vacuumed conditions, dry air conditions (0% RH), and ambient air conditions (40% RH). The different testing conditions have shown different results for the same testing sample. This indicates the nature of DLC film adsorption in ambient air conditions. The chemical composition study has further revealed the adsorbing compounds and the ability of hydrogen and water molecules to get adsorbed on the thin-film surface. This study gives insight into the effect of molecules present in the ambient air on the performance of DLC coatings. It investigates the effect of three DLC coatings deposited using the graphite target onto the Al5051 substrates using DC sputtering.